2020
DOI: 10.1097/md.0000000000020691
|View full text |Cite
|
Sign up to set email alerts
|

Safety of implantable Collamer lens implantation without ophthalmic viscosurgical device

Abstract: To compare the safety of implantable Collamer lens (ICL) implantation with and without ophthalmic viscosurgical device (OVD). A total of 148 eyes underwent a conventional ICL implantation with OVD (OVD group), and 112 eyes underwent a modified ICL implantation without OVD (OVD-free group). The balanced salt solution was used to load ICL and maintain the anterior chamber in the OVD-free group. The surgical time, postoperative uncorrected distance visual acuity, intraocular pressure, endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, newer studies had shown that the OVD-free method is safe and efficient for ICL implantation. It can be a safer method of ICL implantation without additional damage to the corneal endothelial cells compared to the standard method and it completely eliminates ophthalmic viscoelastic devices-related complications without causing additional complications [118][119][120][121][122][123][124].…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…However, newer studies had shown that the OVD-free method is safe and efficient for ICL implantation. It can be a safer method of ICL implantation without additional damage to the corneal endothelial cells compared to the standard method and it completely eliminates ophthalmic viscoelastic devices-related complications without causing additional complications [118][119][120][121][122][123][124].…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…In Peng et al's. ( 15 ) work on OVD-free ICL with anterior chamber irrigation, no significant effect of non-OVD and OVD groups was observed at the 2-year follow-up. In addition, Chen et al ( 12 ) demonstrated that the effect of reducing the OVD on IOP was mainly seen 2–3 h after surgery.…”
Section: Discussionmentioning
confidence: 84%
“…The modified technique could simplify the surgical process, reduce the OVD complications, decrease IOP fluctuations in the early postoperative period, and cause no additional damage to the endothelium compared to the standard technique. Some scholars have also adopted ICL surgery without OVD and have achieved good postoperative results [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%